Effect of Day Time on Cognitive Performances of Preadolescent Athletes Nurtured in a Controlled Environment - Manohar Kumar Pahan; Mahendra Kumar Singh (OVS LLC, 2022)
Research purpose. The study aimed to examine how the cognitive performances of preadolescent sports trainees living and training under a controlled environment are affected during the three different day times. Materials and methods. The research involved 16 male sports trainees from the Jharkhand State Sports Promotion Society, Ranchi, who varied in age from 11 to 14 years and had a minimum of two years of training experience in the same academy. To assess cognitive performance like long-term focused attention, ability to react, logical reasoning, reactive stress tolerance, and visual perception, the TATEENS 2 test set from the Vienna Test System was administered. The percentile ranks of all five tests were compared between three different times of the day. The Friedman test and rANOVA were employed to analyze the data of repetitive measurements. The significance level was set at p < 0.05. Results. The p-values for statistical comparisons of reactive stress tolerance, visual perception, logical reasoning, reaction abilities (reaction time and motor time), and long-term focused attention at three different times of the day were all more than 0.05. Conclusion. Different day times did not significantly affect the cognitive performances of preadolescent sportspersons who lived and trained under similar conditions.